Performance and emission evaluation of a small-bore biodiesel compression-ignition engine. (15th September 2019) - Hirner, Felix Sebastian; Hwang, Joonsik; Bae, Choongsik; Patel, Chetankumar; Gupta, Tarun; Agarwal, Avinash Kumar
Abstract: This study investigates the influence of biodiesels on combustion and emission characteristics in a common-rail equipped small-bore single-cylinder diesel engine. The engine experiments were performed using waste-cooking-oil (WCO), Jatropha-oil, and Karanja-oil derived biodiesels. Conventional diesel was utilized as a baseline fuel. The test engine was operated at a speed of 1200 rpm and an indicated mean effective pressure of 0.5 MPa. The fuels were injected at fuel injection pressures (FIPs) of 40, 80, and 120 MPa. At the same time, the fuel injection timing was varied from −15 crank angle degrees (CAD) after top dead center (aTDC) to −3 CAD aTDC. Experimental results showed that ignition delay was directly correlated to the cetane number and had more significant effect at higher FIPs. The peak of in-cylinder pressure increased as the injection timing was advanced, due to longer ignition delay. Biodiesels showed relatively lower or equal level of nitrogen oxides (NOx) emissions compared to conventional diesel. This was mainly due to lower combustion efficiency showing high amount of smoke, HC, and CO emissions from incomplete combustion. However, for the WCO biodiesel, smoke, HC, and CO emissions could be significantly improved than other biodiesel thanks to better atomization and air-fuel mixing process. Highlights: Jatropha and Karanja biodiesel had shorter ignition delays than diesel. Diesel and WCO biodiesel showed higher portion of pre-mixed combustion. Smoke, CO, and HC emissions from biodiesels were higher than diesel. In most conditions, biodiesel fuels showed lower NOx emissions than diesel.